Effects of low molecular weight hyaluronan combined with carprofen on canine osteoarthritis articular chondrocytes and cartilage explants in vitro - Thippaporn Euppayo (2018)
© 2015, The Society for In Vitro Biology. Intra-articular injection with non-steroidal anti-inflammatory drugs (NSAIDs) is used to treat inflammatory joint disease, but the side effects of NSAIDs include chondrotoxicity. Hyaluronan has shown positive effects on chondrocytes by reducing apoptosis and increasing proteoglycan synthesis. The purposes of this study were to evaluate the effects of low molecular weight hyaluronan (low MW HA), carprofen 25 mg/ml, carprofen 12.5 mg/ml, and a combination of HA and carprofen on canine osteoarthritis (OA) articular chondrocytes and a cartilage explant model in terms of cell viability, extracellular matrix remaining, and gene expression after exposure. In chondrocyte culture, MTT assay was used to evaluate the chondrotoxicity of IC50 and IC80 of carprofen with HA. In cartilage explant culture, two kinds of extracellular matrix (uronic acid and collagen) remaining in cartilage were used to evaluate cartilage damage for 14 d after treatment. Expression of COL2A1, AGG, and MMP3 was used to evaluate the synthesis and degradation of the matrix for 7 d after treatment. In chondrocyte culture, low MW HA could preserve OA chondrocyte viability but could not reduce the chondrotoxicity level of carprofen (P < 0.05). In explant culture, low MW HA combined with 12.5 mg/ml carprofen caused less destruction of uronic acid and collagen structure when compared with the control (P < 0.05). Low MW HA caused high expression levels of COL2A1 and AGG in OA cartilage (P < 0.05); HA combined with carprofen resulted in higher COL2A1 and AGG expression levels than carprofen alone.